Effect of Moringa (Moringa oleifera) Leaf Meal Supplementation in Broiler Chicken Ration on Weight of Internal Organs, HDL and Triglyceride Levels - Ni Ketut Mardewi; Ni Ketut Etty Suwitari; Ni Ketut Sri Rukmini; I Gusti Agung Dewi Seri Rejeki; Ni Made Gemuh Rasa Astiti (Warmadewa University Press, 2017)
This study aims to examine the effect of Moringa leaf meal on broiler chicken ration to the weight of internal organs, triglyceride levels and HDL. The material used in the study was 60 broiler chicken age 2 weeks strain CP707. The design used Completely Randomized Design (RAL) with five treatments and four replications in each treatment. The five treatments are 100% commercial rations without moringa leaf meal as control and 100% commercial rations with 3%, 6%, 9% and 12% moringa leaf meal. Parameters observed included, liver weight, gizzard weight, meat triglyceride levels, and HDL levels of meat. The data obtained were analyzed by completely randomized design. If among the treatments showed significant differences, then the study will be continued by Duncan's multiple-range test. From the results of this study it can be concluded that the addition of moringa leaf meal at level 10% in the ration is the optimal level to decrease the triglyceride of meat without disturbing the HDL content in the meat and the addition of moringa leaf meal up to 12% in the ration does not give a negative effect on the weight of internal organs. Keywords: Broiler Chickens, HDL, Internal Organ, Triglycerides